Análisis de la gestión financiera en la sección de presupuesto del municipio de Montenegro en los años 2008-2011 (2012)
With this project we sought to understand and analyze the management provided by the administration of Mayor in 2008-2011 to finance the Mayor of the Municipality of Montenegro, given that the information provided was taken at constant values by year 2007 for the better implementation of financial indicators, this information was supplied by a municipal official6 *** and which among other things, he applied some laws such as Act 358 of 1997, Act 617 of 2000 and the Act 819 of 2003. In the development of financial indicators were performed using the information in the Primer "National Development Plan", which is supplied to all local authorities, be a useful tool for implementing the final analysis relevant and different from year to year comparisons , which were positive, showing the good management of financial resources of the entity, and secondly to make a global analysis, the city met the standards set by the government, while maintaining good levels without which exceeded the limits that manage laws.